1992
DOI: 10.1093/intimm/4.7.719
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant arthritis and immunity to the mycobacterial 65 kDa heat shock protein

Abstract: The mycobacterial 65 kDa heat shock protein (HSP65) is of critical significance in the model of adjuvant arthritis (AA). Arthritogenic and protective T cell clones obtained from arthritic rats recognized the 180-188 sequence of HSP65. Previous reports have shown that administration of HSP65 prior to disease induction led to resistance to arthritis in the AA model and in several other models of experimental arthritis. Here, we report the development of immunity to HSP65 and the critical 180-188 epitope during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…The arthritogenic role of mycobacterial hsp65 in adjuvant arthritis of rats is well established (1,3), whereas the role of hsp in human RA is seen controversially, although T cell and antibody autoimmunities against hsp60 have been described in RA (52)(53)(54). In adjuvant arthritis the immune reactions against hsp60 have been shown to be protective (55), which is corroborated by recent data from children with juvenile chronic polyarthritis (56,57). Whether hsp70 itself is targeted by the autoimmune response in RA remains to be clarified.…”
Section: Discussionmentioning
confidence: 91%
“…The arthritogenic role of mycobacterial hsp65 in adjuvant arthritis of rats is well established (1,3), whereas the role of hsp in human RA is seen controversially, although T cell and antibody autoimmunities against hsp60 have been described in RA (52)(53)(54). In adjuvant arthritis the immune reactions against hsp60 have been shown to be protective (55), which is corroborated by recent data from children with juvenile chronic polyarthritis (56,57). Whether hsp70 itself is targeted by the autoimmune response in RA remains to be clarified.…”
Section: Discussionmentioning
confidence: 91%
“…It can be induced in susceptible (Lewis) rats by immunization with mycobacterial antigens (20). From several experiments, it can be concluded that T cell responses to HSP play an important immunomodulatory role in the induction of AIA (21). First, it was shown that AIA can be passively transferred by T cells from diseased rats to syngeneic disease-free animals (22).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of HSP60 might also explain the development of an autoimmune response to this protein because overexpression might go along with altered localization of this normally mitochondria-localized protein [28,29]. Similarly to HSP60 expression, the presence of an autoimmune response directed to HSP60 is associated with a protective rather than a pathogenic effect in both adjuvant and human arthritis [30,31,32]. …”
Section: Heat Stress and Heat Shock Proteinmentioning
confidence: 99%